2019
DOI: 10.1002/ccr3.2412
|View full text |Cite
|
Sign up to set email alerts
|

Bone metastasis as primary presentation of pancreatic ductal adenocarcinoma: A case report and literature review

Abstract: PDAC bone metastases represent a clinical challenge characterized by multifaceted biological entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
(85 reference statements)
0
12
0
Order By: Relevance
“…However, there are only a few reports combining basic research and clinical aspects of MSPC. Therefore, it is necessary to encourage the enrollment of patients in clinical trials, including their genetic and molecular characterization, and to combine standard chemotherapy utilizing treatment by bone-modifying agents with MSPC is a clinical challenge with unexplained biological characteristics (32). The systemic treatment of MSPC would be an exciting and promising research topic.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are only a few reports combining basic research and clinical aspects of MSPC. Therefore, it is necessary to encourage the enrollment of patients in clinical trials, including their genetic and molecular characterization, and to combine standard chemotherapy utilizing treatment by bone-modifying agents with MSPC is a clinical challenge with unexplained biological characteristics (32). The systemic treatment of MSPC would be an exciting and promising research topic.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Furthermore, Argentiero et al . reported a PDAC patient with metastatic lesions in L3, T10, T11, the right iliac wing and crest, left clavicle, and bilateral ribs,[ 1 ] while an additional study reported a patient with severe lower back pain and osteoblastic lumbar vertebral lesions. [ 7 ] Finally, Rades et al .…”
Section: Discussionmentioning
confidence: 99%
“… 124 In pancreatic cancer, the most common metastatic site is the liver, followed by the lungs, peritoneum, and bones. 125 – 127 Recently, Lee et al reported that activation of STAT3 in hepatocytes and the subsequent production of serum amyloid A1 and A2 in the bloodstream direct pancreatic cancer liver metastasis. 128 Interestingly, lineage-tracing analysis in a mouse model of pancreatic cancer revealed that metastases in the lung and liver are monoclonal, whereas those in the peritoneum and diaphragm tend to be polyclonal.…”
Section: Characteristics Of Pancreatic Cancermentioning
confidence: 99%